From logos to the metaverse. Approach to the concept of Existence in Education - Bedoya-Ávalos, José Rolando; Rosales-Cevallos, Marco Mauricio; Arcia-Hernández, Pedro; García-Manríquez, Mauricio Agustín; Eguigure-Torres, Yenny Aminda; Sánchez-Babilonia, Juliana; Galleguillos-Madrid, Felipe Marcelo; García-Celis, Segundo Wilmar; Casanueva-Yánez, Galvarino (Journal of Posthumanism, 2025)
Defining existence has long been an epistemological conflict that has kept disciplines at odds. In the field of education specifically, the ages of knowledge have superimposed a significant weight that has not collaborated with the uniform conceptual dialogic, but rather, on the contrary, has increased the gap that today, more than ever, distances the subject from the assumption of absolute truth. Thus, for example, the transition from myth to logos allows existence to be described as mythological in ancient times, later surpassed by existence as divine in the medieval age, until reaching the biological conception of the term (modern age). This paper seeks to reflect on the conception of existence today and within which the concept of education is inscribed. Its purpose is to interpret a conceptual assumption of education and its fabrics of social coexistence where corporality is not a sine qua non requirement. As a finding, it stands out that the metaverse in education is the systematization of immersive experiences mediated by technologies that promote autonomous and leading learning of and among students without the weight of space and distance as conventional restrictions to grow.